Influência do estresse hídrico e salino na germinação de urochloa decumbens e urochloa ruziziensis - Rocha Pereira, Maria Renata [UNESP] (2012)
Studies of the germination response of seeds subjected to artificial stresses are provided tools for better understanding of the survivability and adaptation of these species in natural stress conditions such as drought or saline soils, common in agricultural and forest regions, contributing significantly to the development of management strategies. Thus, the purpose of this study was to evaluate the possible effects of water and salt stress on germination of Urochloa decumbens and Urochloa ruziziensis. The test was conducted at the Faculty of Technology of São Paulo, campus of Capon Bonito. The seeds were sown with four replicates of 50 seeds in paper soaked in solutions with the potentials of 0.0, -0.2, -0.4 and -0.8 MPa, induced with polyethylene glycol (PEG 6000) and NaCl. The germination test was conducted at 25 degrees C in the presence of light, evaluating the first test score at seven days after sowing, and weekly germination (normal seedlings) until 35 days. We calculated the index of germination rate. The results allowed the conclusion that water stress causes a greater reduction in force, speed of germination and cumulative germination of seeds of U. decumbens and U. ruziziensis than salt stress. The species U. decumbens showed higher tolerance to water and salt stresses.